2017
DOI: 10.3389/fpsyt.2017.00246
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Control-Related Functional Brain Networks in Drug-Naive Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disease featuring executive control deficits as a prominent neuropsychological trait. Executive functions are implicated in multiple sub-networks of the brain; however, few studies examine these sub-networks as a whole in ADHD. By combining resting-state functional MRI and graph-based approaches, we systematically investigated functional connectivity patterns among four control-related networks, including the frontoparietal network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 78 publications
(81 reference statements)
3
28
1
Order By: Relevance
“…Alterations of small‐world topological properties have also been reported in three previous functional connectome studies of ADHD children (Tao et al, ; Wang et al, ; Xia et al, ), but the results were not fully consistent. The results of a smaller‐sample study using drug‐naïve ADHD children were consistent with our results in showing a decreased global efficiency in ADHD (Tao et al, ). However, in the other two studies using drug treated samples, no significant changes in global efficiency in ADHD were found, and opposite changes in local efficiency were observed.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Alterations of small‐world topological properties have also been reported in three previous functional connectome studies of ADHD children (Tao et al, ; Wang et al, ; Xia et al, ), but the results were not fully consistent. The results of a smaller‐sample study using drug‐naïve ADHD children were consistent with our results in showing a decreased global efficiency in ADHD (Tao et al, ). However, in the other two studies using drug treated samples, no significant changes in global efficiency in ADHD were found, and opposite changes in local efficiency were observed.…”
Section: Discussionmentioning
confidence: 78%
“…Alterations of small-world topological properties have also been reported in three previous functional connectome studies of ADHD children (Tao et al, 2017;Wang et al, 2009;Xia et al, 2014), but the results were not fully consistent. The results of a smaller-sample study using drug-naïve ADHD children were consistent with our results in showing a decreased global efficiency in ADHD (Tao et al, 2017).…”
Section: Associations Between Clinical Variables and Graph Measuresmentioning
confidence: 72%
“…31 This is consistent with previous research that found evidence for altered CON connectivity in association with neurodevelopmental symptoms. [54][55][56] Impaired anticorrelations between both CON and 'Other' and DAN and 'Other' networks may be reflective of impairments in neural functional integration that may contribute to neurodevelopmental symptoms. Also higher neurodevelopmental symptoms were associated with greater connectivity between the CON and VAN networks, which may be indicative of increased attention to external environmental stimuli, consistent with some previous research on inattentive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals diagnosed with ADHD have shown dysfunction of the anterior cingulate cortex (ACC) (Schneider, Retz, Coogan, Thome, & Rösler, 2006) and lowered beta/theta ratios, particularly in the PFC region (Arns, Conners, & Kraemer, 2013). This dysregulation is associated with disruption of interactions between the default mode network and the FPN-CON (Tao et al, 2017). Together, this information implicates the top-down network in a regulatory role over the bottom-up network in sustained attention.…”
Section: Sustained Attentionmentioning
confidence: 99%